Licensing Policy on Mineral and Coal Mining in the Concept of Division of Authority (Universitas Negeri Semarang, 2022)
The mineral and coal mining licensing policy currently in force is law Number 3 of 2020 concerning Amendments to law Number 4 of 2009 concerning Mineral and Coal Mining. However, this policy is considered too centralistic because the role of the Central Government is more dominant than the Role of the Local Government. This research uses a normative approach to analyze related licensing policies in the Mineral and Coal Law in the concept of division of authority. The results show that in the provisions of the legislation, the central government has the authority to grant permits for minerals and coal mining. In contrast, local governments can obtain power through delegation from the central government. This policy tends to be centralistic, even though the Indonesian state adheres to the principle of decentralization. The government needs to consider several things, such as the policy implementation needs to pay attention to the “content of the policy” and “context of implementation.